PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR PPKn SISWA KELAS VI B SD NEGERI 002 KIYAP JAYA KECAMATAN BANDAR SEI KIJANG KABUPATEN PELALAWAN - Alfani ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low student learning outcomes PPKn SD Negeri 002Kirap Jaya sixth grade students, this is evidenced by an average of only 62.14 studentlearning outcomes. While KKM is set at 65. To the researchers conducted a study with theaim to improve learning outcomes PPKn through the implementation of cooperative learningmodel type STAD. This research is a classroom action through the stages of planning,implementing action, observation and reflection. This research was conducted in two cycles.The subjects were students of class VI SD Negeri 002 Kirap Jaya with a number of studentssebanya 40 students. The results of the research data showed that the learning outcomes ofstudents has increased, this is evidenced by: (a) the activities of teachers has increased in thefirst cycle of the first meeting activity for teachers to get a score of 11 (45.83%), in the firstcycle II meeting increased with a score of 14 ( 58.33%), the second cycle of the first meetingincreased with a score of 19 (79.19%). And the second cycle II meeting increased with ascore of 22 (91.66%). Activities of students has increased, at the first meeting the first cycle ofactivity students obtain a score of 10 (41.66%), at a meeting of the second cycle II with ascore of 13 (54.16%), at a meeting I cycle II with a score of 17 (70, 83%). And at the secondmeeting of the cycle II with a score of 20 (83.33%); and (b) PPKn learning outcomes ofstudents has increased At the base score / baseline number of students who completed is 20students (50.00%) with a low category, the first cycle is the number of students who pass the30 students (75.00%) with high category and the second cycle the number of students whopass the increase with the amount due totaling 36 students (90.00%) with a very highcategory.